The Comparative Effectiveness of Angiotensin II Receptor Blockers and Angiotensin-Converting Enzyme Inhibitors in Outpatient Hypertensive Patients at Community Health Centers - Prasetyawan, Fendy; Yuneka Saristiana; Faisal Akhmal Muslikh; Wisnu Haryo Widyoko; Chandra Arifin; Abd Rofiq (PT FORMOSA CENDEKIA GLOBAL, 2024)
Hypertension, often termed